2018
DOI: 10.1007/s12035-018-1008-x
|View full text |Cite
|
Sign up to set email alerts
|

The Synthetic Steroid Tibolone Decreases Reactive Gliosis and Neuronal Death in the Cerebral Cortex of Female Mice After a Stab Wound Injury

Abstract: Previous studies have shown that estradiol reduces reactive gliosis after a stab wound injury in the cerebral cortex. Since the therapeutic use of estradiol is limited by its peripheral hormonal effects, it is of interest to determine whether synthetic estrogenic compounds with tissue-specific actions regulate reactive gliosis. Tibolone is a synthetic steroid that is widely used for the treatment of climacteric symptoms and/or the prevention of osteoporosis. In this study, we have assessed the effect of tibolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 99 publications
(123 reference statements)
1
23
0
Order By: Relevance
“…In this regard, astrocytes are postulated as mediators of the action of tibolone in the CNS [118]. Indeed, a recent study has shown that tibolone reduces reactive astrogliosis in a model of TBI in ovariectomized female mice [169]. …”
Section: The Cns As a Target For Neuroprotective Estrogenic Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, astrocytes are postulated as mediators of the action of tibolone in the CNS [118]. Indeed, a recent study has shown that tibolone reduces reactive astrogliosis in a model of TBI in ovariectomized female mice [169]. …”
Section: The Cns As a Target For Neuroprotective Estrogenic Compoundsmentioning
confidence: 99%
“…In vivo studies have shown that several estrogenic compounds, such as estradiol, phytoestrogens (genistein), some SERMs and tibolone, decrease reactive astrogliosis and glial scar formation after TBI [123, 169-171, 199-201]. After spinal cord injury, tamoxifen has been shown to first increase astrogliosis at day 2 after injury and then gradually decrease astrogliosis [202].…”
Section: Neuroprotective Actions Of Estrogenic Compounds After Tbimentioning
confidence: 99%
“…Previous studies have shown that tibolone 3-hydroxy metabolites activate ERs in human primary astrocytes [19] and that ERs, mainly ERβ, mediate different actions of tibolone on T98G astrocyte-like cells [14,15]. The direct actions of tibolone on astrocytes and astrocyte-like cells through ERs, together with the decreased neuronal loss in association with a reduction of reactive astrogliosis in the injured cortex of tibolone-treated mice [16], suggest that astrocytes may be involved in the neuroprotective actions of the steroid. Indeed, it is known that astrocytes mediate the neuroprotective actions of estradiol and other ER ligands in different CNS (central nervous system) pathologies [20,21].…”
Section: Introductionmentioning
confidence: 96%
“…Thus, the steroid reduces inflammation and prevents oxidative damage in BV-2 microglia exposed to palmitic acid [11] and protects T98G cells from glucose deprivation and palmitic acid toxicity [12][13][14], reducing oxidative stress and preserving mitochondrial membrane potential [14,15]. Furthermore, tibolone decreases in vivo the reactive response of microglia and astrocytes after a stab wound lesion of the cerebral cortex in ovariectomized female mice [16].…”
Section: Introductionmentioning
confidence: 97%
“…Having in account the importance of astrocytes for brain inflammation, and the promising effects of tibolone for astrocytic and neuronal protection (Crespo-Castrillo et al, 2018), we developed a genomic-scale metabolic model of astrocytes, with the purpose of enlighten the metabolic pathways modulated by tibolone during an inflammatory response caused by the increased uptake of palmitate. We focused or attention, in the identification of metabolic changes related with the modulation of cytokines, the release of gliotransmitters and the neuroprotective effects mediated by tibolone in an inflammatory scenario (Wojtal et al, 2006).…”
Section: Introductionmentioning
confidence: 99%